Formation of supermassive stars in the first star clusters - Reinoso, Bastián; Klessen, Ralf S.; Schleicher, Dominik R. G.; Glover, Simon; Solar, P (Monthly notices of the Royal Astronomical Society, 2023)
The formation of supermassive stars is believed to be an essential intermediate step for the formation of the massive black hole seeds that become the supermassive black holes powering the quasars observed in the early Universe. Numerical simulations have shown that supermassive stars can form in atomic-cooling haloes when protostars reach accretion rates higher than ∼10−2 M⊙ yr−1 and fragmentation is suppressed on pc scales. It is, however, still uncertain if a supermassive star still emerges when fragmentation occurs at smaller scales and a cluster of stars is formed instead. In this work, we explore the problem of massive object formation due to the interplay of collisions and accretion in star clusters at low metallicity. We model a small embedded cluster of accreting protostars following subparsec scale fragmentation during the collapse of a primordial gas cloud, and follow its evolution by performing N-body plus hydrodynamical simulations. Our results show that supermassive stars with 103 and 104 M⊙ are always formed due to the interplay of collisions and accretion, and in some cases these objects are part of a binary system. The resulting supermassive star is surrounded by tens of smaller stars with typical masses in the range 1-100 M⊙.
Gesehen am 19.06.2023